Iteratively Decoded Variable Length Space-Time Coded Modulation: Code Construction and Convergence Analysis - Ng, S.X.; Wang, J.; Tao, M.; Yang, L.-L.; Hanzo, L. (IEEE transactions on wireless communications, 2007)
An iteratively decoded variable length space time coded modulation (VL-STCM-ID) scheme capable of simultaneously providing both coding and iteration gain as well as multiplexing and diversity gain is proposed. Non-binary unity-rate precoders are employed for assisting the iterative decoding of the VL-STCM-ID scheme. The discrete-valued source symbols are first encoded into variable-length codewords that are mapped to the spatial and temporal domains. Then the variable-length codewords are interleaved and fed to the precoder assisted modulator. More explicitly, the proposed VL-STCM-ID arrangement is a jointly designed iteratively decoded scheme combining source coding, channel coding, modulation as well as spatial diversity/multiplexing. As expected, the higher the source correlation, the higher the achievable performance gain of the scheme becomes. Furthermore, the performance of the VL-STCM-ID scheme is about 14.6 dB better than that of the fixed length STCM (FL-STCM) benchmarker at a source symbol error ratio of 10 -4